Revenue Implications of a Progressive-Rate Tax on Expenditures: A Study of Selected Aspects of Irving Fisher's Proposal to Eliminate Savings from the Income Tax Base - Harriss, C. Lowell (The Review of Economics and Statistics, 1943)
C. Lowell Harriss, Revenue Implications of a Progressive-Rate Tax on Expenditures: A Study of Selected Aspects of Irving Fisher's Proposal to Eliminate Savings from the Income Tax Base, The Review of Economics and Statistics, Vol. 25, No. 3 (Aug., 1943), pp. 175-191